2001
DOI: 10.1161/hc4001.097037
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia After Cardiac Arrest

Abstract: Background-No proven neuroprotective treatment exists for ischemic brain injury after cardiac arrest. Mild-to-moderate induced hypothermia (MIH) is effective in animal models. Methods and Results-A safety and feasibility trial was designed to evaluate mild-to-moderate induced hypothermia by use of external cooling blankets after cardiac arrest. Inclusion criteria were return of spontaneous circulation within 60 minutes of advanced cardiac life support, hypothermia initiated within 90 minutes, persistent coma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…(17)(18)(19)(20)(21) Ideal cooling procedures must quickly and practically reach the target temperature, without causing injuries.…”
Section: How To Cool the Patient?mentioning
confidence: 99%
See 1 more Smart Citation
“…(17)(18)(19)(20)(21) Ideal cooling procedures must quickly and practically reach the target temperature, without causing injuries.…”
Section: How To Cool the Patient?mentioning
confidence: 99%
“…(18) Application of ice packs has proven efficient, reducing on the average 0.9° C per hour of application. (19) Probably, the most practical and agile method is intravenous infusion of iced fluid (at 4°C). Rajek et al (20) administered iced saline solution (4°C) to volunteers at a speed of 40 mL/kg, 30 minutes by means of central catheter and it was possible to safely achieve a 5°C reduction of central temperature per hour.…”
Section: How To Cool the Patient?mentioning
confidence: 99%
“…Felberg et al reported a feasibility trial where external cooling was feasible and safe. However, external cooling was slow and imprecise and efforts to speed up the start of cooling and to improve the cooling process are needed (Felberg et al 2001).…”
Section: Hypothermia After Cardiac Arrestmentioning
confidence: 99%
“…Recent trials have administered sedative and neuromuscular blocking agents during the hypothermia interval. l4, 15,20,21 Neuromuscular blockade is given to prevent shivering during hypothermia. Modest hypothermia has been induced in un-intubated stroke patients without resorting to the use of neuromuscular blockade or sedation.…”
mentioning
confidence: 99%
“…Multiple techniques of hypothermia induction have been published including: application of ice packs; 5 surface cooling with cooled forced-air, 4,20 or circulating water blankets; 18,19 infusion of 4°C iv fluids; [26][27][28] immersion in cold water; 29 specialized endovascular cooling devices; 21,30,31 and cardiopulmonary bypass. 32 No trials comparing hypothermia techniques in cardiac arrest patients have been published.…”
mentioning
confidence: 99%